2021
DOI: 10.14719/pst.2021.8.3.1117
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, pharmacological and tissue culture studies of some important species of the genus Barleria L. (Acanthaceae) - a review

Abstract: Ayurvedic sciences helped the early humans to overcome chronic dangerous diseases. There are thousands of varieties of herbs and medicinal plants used to overcome such dreadful diseases. The genus Barleria L. belongs to family Acanthaceae, a medicinally significant group of plants having diversified phytochemicals used for different pharmacological properties. It has been utilized since ancient times for medicinal purposes. It has many plant secondary metabolites such as terpenes, flavonoids, lignins, alkaloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Acanthaceaea Leaf Hexadecanoic acid, ethyl 9,12,15octadecatrienoate Methanolic Assist cell mediate immune response [42].…”
Section: Methanolicmentioning
confidence: 99%
“…Acanthaceaea Leaf Hexadecanoic acid, ethyl 9,12,15octadecatrienoate Methanolic Assist cell mediate immune response [42].…”
Section: Methanolicmentioning
confidence: 99%
“…Extensive literature survey showed that Barleria is medicinally important genus and locally called as Vajradanti ( Banerjee et al, 2012 ). The plant is widely used in the treatment of human diseases like anemia, toothache, cough, fever, asthma, bronchitis, diabetes, insect bites and inflammations ( Banerjee et al, 2012 ; Sudheer and Praveen, 2021 ). Aerial parts and leaves of Barleria are known to be a vital source of iridoids ( Amoo et al, 2011 ; Sudheer and Praveen, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The plant is widely used in the treatment of human diseases like anemia, toothache, cough, fever, asthma, bronchitis, diabetes, insect bites and inflammations ( Banerjee et al, 2012 ; Sudheer and Praveen, 2021 ). Aerial parts and leaves of Barleria are known to be a vital source of iridoids ( Amoo et al, 2011 ; Sudheer and Praveen, 2021 ). The leaves of the plant are known for flavonoids, saponins, sterols, tannins, and terpenoids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several species of Barleria are known for their medicinal or ornamental values [ 37 , 52 , 53 ]. There have been studies reviewing the traditional, phytochemical and pharmacological properties of specific species of Barleria (e.g., B. lupulina and B. prionitis ) [ 54 , 55 , 56 ], however none have comprehensively reported on species within Barleria using exisiting literature in a clear and concise manner. Therefore, this review is intended to elaborate on only the important and extensively studied species belonging to the genus Barleria , with an emphasis on their biological activities that have been published.…”
Section: Introductionmentioning
confidence: 99%